Системне проектування інформаційно-аналітичних досліджень за принципами індуктивних методів моделювання - Осипенко, В.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
In article the new methodological approach displaying a projection of fundamental bases of inductive modeling methods of complex systems, on the one hand and modern system principles of project management, on the other hand, on a plane of complex information-analytical researches is considered. This approach is expedient for using in complex very expensive analytical researches in the field of economy, ecology, sociology, the international relations and many other things adjacent directions. Nevertheless, as the system technological scheme it also can be applied to more simple analytical problems.